Pengembangan Sistem Informasi untuk Meningkatkan Kualitas Pelayanan Publik di Kelurahan Kampung Tengah - Mujiono Mujiono; Fitrah Ramadhani Siregar; Aulia Rahmah; Muhammad Fajar Aqila; Rauda Rossa Tambunan; Ahmad Dani; Nesha Zahro Aqila; Elsa Priskariaty; Dilla Fadillah; B Bintang Prakarsa; Alfridho Saputra (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
The Village/Urban Information System is a forum that contains information on population data, public services and information about village/kelurahan activities and programs managed by the village/urban government to support better village development. In the village of Central Village, Sukajadi District, Pekanbaru City, the information system is still not maximal, so it needs to be updated and developed. The purpose of this community service is to update the existing information system in the Central Village Village, both population data, village location maps and village structures. This is done by using a population census, filling in population data on the website and updating the location map and village structure. The results obtained are that the village information system has been updated so as to improve public services.